(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Learning research during the Covid-19 pandemic era. Learning online (online) is considered to be a solution for distance teaching and learning activities. With the LSQ (Learning Stars with a Question) learning method, the object of research was the fourth semester of Electrical Engineering students of UNISNU Jepara in mathematics subject II from February-April 2020. Researchers took seven detailed meetings three times face to face (TMK) before the pandemic. Covid-19 and four Indirect Face-to-Face (TMtL) meetings during the Covid-19 pandemic, the online LSQ learning method, WA media (WhatsApp). Based on the lecture contract, an agreement is made on the proportion of assessments: 10% attendance, 20% activeness, 15% Independent Assignments, 30% Mid-Semester Exams, and 25% Final Semester Examinations. Realization in seven meetings with three times the TMK, and four times the TMtL were detailed results for the presence of meanTMK <meanTMtL, meanTMK <meanTMtL activity, meanTMK <meanTMtL activity. From these results, it can be concluded that the basic learning method of LSQ in TMtL shows more results than TML.